2013
DOI: 10.1108/00368791311303456
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of turbulent lubrication in plain full journal bearings

Abstract: PurposeThe purpose of this paper is to assess the turbulent thermohydrodynamic (THD) performance characteristics of an axially grooved finite journal bearing for a variety of simulated operating conditions.Design/methodology/approachThe set of governing equations consisting the Navier‐Stokes, turbulent kinetic energy and its dissipation rate equations coupled with the energy equation in the lubricant flow and the heat conduction equation for the bush are solved to obtain the three dimensional steady state THD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In 2005 Braunetiere [7], show that a number of theories for the turbulent lubrication film exist which are based on various well-established models of turbulent flow. Solghar and Nassab (2013) [8] carry out a study in to assess the turbulent thermohydrodynamic (THD) performance characteristics of an axially grooved finite journal bearing [8,9]. They are mentioned in their research that the bearing of the operating characteristics are significantly changed by increasing the Reynolds number.…”
Section: Turbulent Flow Effect In Plain Bearingmentioning
confidence: 99%
“…In 2005 Braunetiere [7], show that a number of theories for the turbulent lubrication film exist which are based on various well-established models of turbulent flow. Solghar and Nassab (2013) [8] carry out a study in to assess the turbulent thermohydrodynamic (THD) performance characteristics of an axially grooved finite journal bearing [8,9]. They are mentioned in their research that the bearing of the operating characteristics are significantly changed by increasing the Reynolds number.…”
Section: Turbulent Flow Effect In Plain Bearingmentioning
confidence: 99%
“…Also, in order to assess the impacts of turbulent conditions on the bearing THD performance, a modified low-Re k–ε turbulence model was used. 11–18…”
Section: Introductionmentioning
confidence: 99%
“…He found that the fluid inertia has significant influence on THD characteristics of journal bearing for the conditions that the bearing runs under low load, high speed, and large clearance conditions such that the Reynolds lubrication theory is no longer suitable for the prediction of the bearing performance. Arab Solghar and Gandjalikhan Nassab [15][16][17] have dealt with three-dimensional simulation of the flow field of the journal bearings under the turbulent regime. The turbulent Fow within the bearing was modeled exploiting a modified low-Re k-" turbulence model.…”
Section: Introductionmentioning
confidence: 99%